2017
DOI: 10.2174/1389201018666170808122531
|View full text |Cite
|
Sign up to set email alerts
|

Random Start Ovarian Stimulation for Oocyte or Embryo Cryopreservation in Women Desiring Fertility Preservation Prior to Gonadotoxic Cancer Therapy

Abstract: The current review suggests that random start ovarian stimulation can shorten the interval between ovarian stimulation and oocyte retrieval, with the yield of oocytes and embryos being comparable to conventional stimulation protocols. Thus, random start ovarian stimulation may serve as a better option for fertility preservation in patients requiring urgent cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 0 publications
1
38
0
2
Order By: Relevance
“…Over the years, further improvements aiming to increase the efficacy and safety of FP have been introduced at our center. They include the use of ovarian stimulation regimens incorporating aromatase inhibitors for women with hormone‐sensitive breast cancer and implementation of random‐start COS protocols aimed at shortening the delay in retrieving oocytes …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, further improvements aiming to increase the efficacy and safety of FP have been introduced at our center. They include the use of ovarian stimulation regimens incorporating aromatase inhibitors for women with hormone‐sensitive breast cancer and implementation of random‐start COS protocols aimed at shortening the delay in retrieving oocytes …”
Section: Methodsmentioning
confidence: 99%
“…They include the use of ovarian stimulation regimens incorporating aromatase inhibitors for women with hormone-sensitive breast cancer 11,12 and implementation of random-start COS protocols aimed at shortening the delay in retrieving oocytes. [13][14][15][16] The option of CoOT has been presented to all women and particularly discussed when time constraints or concerns regarding hormonal stimulation were present. Laparoscopic retrieval for…”
Section: Reproductive Counseling Of Adult Womenmentioning
confidence: 99%
“…Danis et al [29] published a systematic review of 19 studies published between January 2000 and June 2017 to evaluate the utility of random-start ovarian stimulation for fertility preservation. This recent review suggested that random-start stimulation was associated with a reduced time interval between the initiation of ovarian stimulation and oocyte or embryo cryopreservation.…”
Section: Random-start Ovarian Stimulationmentioning
confidence: 99%
“…At the same time, with the improvements in cancer treatment, oocyte freezing has gained importance for patients who are diagnosed with cancer at an early age and desire to maintain fertility. Other factors that reduce fertility include having a poor ovarian reserve, a history of early menopause in the family, systemic disease (Systemic lupus erythematosus, rheumatoid arthritis groups) that have to be put on lifelong immunosuppression and having advanced stage endometriosis that requires oophorectomy and disrupts the quality of life (1,2). Fertility protection procedures are prominent for this group of patients.…”
Section: Introductionmentioning
confidence: 99%